Readiness to change drinking behaviour among heavy-drinking university students in England. (2014) - Longstaff, Fran; Heather, Nick; Jankowski, Mark; Allsop, Susan; Wareham, Helen; Partington, Sarah; Partington, Elizabeth; Gibson, Alan St Clair
No abstract available